تصور مقترح لتطوير السياسات التعليمية لتحقيق التنمية المستدامة من وجهة نظر القيادات العليا في وزارة التربية والتعليم بسلطنة عمان - جابري، وليد محمد حمد
This study aimed to develop a proposed vision for developing educational policies and frameworks for exploring curricula to achieve sustainable development from the viewpoint of senior leaders in the Ministry of Education in the Sultanate of Oman، using the qualitative qualitative approach. The study deals with the problem of the topic of research and answering its questions according to two frameworks (theoretical and practical). The theoretical framework includes a survey of previous studies and literature related to the topic. As for the practical aspect of the study، it is the views of applying research tools to an intentional sample from the top leaders of the Ministry of Education in the Sultanate of Oman and its size (30) of leaders. In order to achieve the goals of the study، the researcher developed the study tools، which is a survey interview to verify the study problem، and analyze the content of the general philosophy document for education in the Sultanate of Oman، in addition to the practical aspect of analyzing the results through the( Maxqda) qualitative analysis program، discussing and linking them to educational literature and previous studies، then Submit recommendations and suggestions related to the results of this study، and through the opinions and contributions of the research sample from the higher educational leaders who have a lot in this field in extracting a set of forward-looking frameworks for the educational curricula، which can be as a national document that contributes to the field of preparing educational curricula according to future developments، the most important of which is that the country's constitution and national identity is the source The first is to approach the curriculum، and that the Sultanate's vision 2040 and the accompanying developmental measures in all axes are one of the foundations of exploring the curricula in addition to the wishes and needs of society and the accompanying qualification of the student scientifically، intellectually and skillfully.